The neural correlates of auditory and visuospatial span in logopenic progressive aphasia and Alzheimer's disease. (October 2016) - Foxe, David; Leyton, Cristian E.; Hodges, John R.; Burrell, James R.; Irish, Muireann; Piguet, Olivier
Abstract: Introduction: Logopenic progressive aphasia (lv-PPA) is a form of primary progressive aphasia and is predominantly associated with Alzheimer's disease (AD) pathology. The neuropsychological profiles of lv-PPA and typical clinical AD are, however, distinct. In particular, these two syndromes differ on attention span measures, where auditory attention span is more impaired in lv-PPA than in AD and visuospatial span appears more impaired in AD than in lv-PPA. The neural basis of these span profiles, however, remains unclear. Method: Sixteen lv-PPA and 21 AD matched patients, and 15 education-matched healthy controls were recruited. All participants were assessed by a neurologist and completed a neuropsychological assessment that included the Wechsler Memory Scale–III Digit and Spatial Span tasks, and underwent a high-resolution structural brain MRI to conduct cortical thickness analyses. Results: Patient groups were impaired on all span tasks compared to Controls. In addition, performance on Digit Span Forward (DSF) was significantly lower in the lv-PPA than the AD group, while Spatial Span Forward (SSF) was significantly lower in the AD than the lv-PPA group. No differences were found between patient groups on the Digit or Spatial Span Backward tasks. Neuroimaging analyses revealed that reduced DSF performance correlated to thinning of the left superior temporal gyrus in the lv-PPA group, whereas reduced SSF performance was related to bilateral precentral sulcus and parieto-occipital thinning in the AD group. Analyses of the backward span tasks revealed that reduced Spatial Span Backward (SSB) performance in the lv-PPA group related to cortical thinning of the left superior parietal lobule. Conclusions: This study demonstrates that while lv-PPA and AD commonly share the same underlying neuropathology, their span profiles are distinct and are mediated by divergent patterns of cortical degeneration.